Engineering GaN nanowire photoanode interfaces for efficient and stable photoelectrochemical water splitting. (November 2022) - Abdullah, Ameer; Bagal, Indrajit V.; Waseem, Aadil; Kulkarni, Mandar A.; Thaalbi, Hamza; Lee, June Key; Ryu, Sang-Wan
Abstract: GaN has been investigated as a photoanode for photoelectrochemical (PEC) water splitting; however, its practical applicability is limited owing to its poor stability and low solar-to-hydrogen conversion efficiency. One of the most effective approaches to address poor stability and low-efficiency concerns is to load cocatalysts and passivation layers onto the GaN surface. In this work, a ternary sandwiched nanostructure of ZnS/Au NPs/GNW (GaN nanowire) is fabricated and tested as a photoanode for photoelectrochemical water splitting by integrating a crystalline GNW core, metallic Au nanoparticles (NPs), and an amorphous ZnS overlayer. Under one sun illumination, the ZnS/Au NPs/GNW photoanode exhibits a 2.25-fold increase (1.15 mA cm −2 ) in the photocurrent density at zero bias versus the reference electrode relative to bare GNW. The sandwiched nanostructure photoanode revealed a considerable improvement in stability after 14 h of continuous stability testing, with 76% retention. Based on systematic investigations, it is proposed that Au NPs and GNW core inject photogenerated holes into the ZnS overlayer, and then the ZnS overlayer facilitates the hole injection into the electrolyte. Thus, the remarkably improved photoelectrochemical water splitting performance of ZnS/Au NPs/GNW photoanode is attributed to the significantly suppressed bulk and surface charge recombination, owing to the relayed pumping of the photogenerated charge carriers through the photoanode/electrolyte interfaces developed by Au NPs and ZnS overlayer. Graphical abstract: Image 1 Highlights: Plasmonic nanoparticles sandwiched ZnS/Au/GaN nanowire photoanode is fabricated. The photocurrent density is increased by 2.25 times for solar water splitting. Role of overlayer and Au NPs in enhancement of solar water splitting is explained. Sandwiched structure photoanode showed 76% current retention in ∼14 h. Mechanism to explain the PEC water splitting performance is proposed.